Which transfer day results in the highest live birth rate for PCOS patients undergoing in vitro fertilization? - Yuying Guo; Fangfang Dai; Bo Zheng; Linlin Tao; Tieqing Cui (BMC Pregnancy and Childbirth, 2023)
Abstract Background Polycystic ovary syndrome (PCOS) has unusual levels of hormones. The hormone receptors in the endometrium have a hostile effect and make the microenvironment unfavorable for embryo implantation. The use of gonadotropin stimulation during in vitro fertilization (IVF) may have an impact on embryo implantation and live birth rate. According to recent data, the clinical results of day 4 embryo transfer (D4 transfer) were on par with those of day 5 embryo transfer (D5 transfer) in IVF-ET. There are few studies comparing the outcomes of transplants with various etiologies and days. The purpose of this study was to determine which transfer day had the best result for PCOS patients undergoing IVF. Methods This retrospective cohort study was conducted in the Xingtai Infertility Specialist Hospital between January 2017 and November 2021. A total of 1,664 fresh ART cycles met inclusion criteria, including 242 PCOS transfers and 1422 tubal factor infertility transfers. Conclusions PCOS individuals had the highest live birth rate on D4 transferred. It was not need to culture embryos to blastocysts to optimize embryo transfer for PCOS women. This could be a novel approach to transplantation for PCOS.